Plasma miR-208b and miR-499: Potential Biomarkers for Severity of Coronary Artery Disease. (22nd November 2019) - Wang, Wei; Li, Tai; Gao, Lei; Li, Yang; Sun, Ying; Yao, Heng-Chen
Abstract : Aims. MicroRNAs (miRNAs) are associated with the pathogenesis of coronary artery disease (CAD). The objective of this study is to explore plasma levels of miR-208b and miR-499 in CAD and analyze its association with the severity of CAD. Materials and Methods. 195 consecutive CAD patients who underwent coronary angiography were enrolled in this study. Severity of coronary lesions was evaluated by the synergy between percutaneous coronary intervention with taxus and cardiac surgery score (SYNTAX) score (SS). Plasma levels of miR-208b and miR-499 were assessed by quantitative real-time polymerase chain reaction (qRT-PCR). The relationship between miR-208b and miR-499 and SS was analyzed. Results. The qRT-PCR results showed that plasma levels of miR-208b and miR-499 in SS > 32 (high SS) group was higher than those in low (SS ≤ 22 ) and intermediate (22 < SS ≤ 32 ) groups. Meanwhile, plasma miR-208b and miR-499 levels were significantly positive correlated with the SS (Spearman's r = 0.535 and r = 0.407, respectively; both p < 0.001 ). Multivariate logistic analysis results showed that miR-208b (odds ratio [OR]: 2.069; 95% confidence interval [CI]: 1.351-3.167; p = 0.001 ) and miR-499 (OR: 1.652; 95% CI: 1.222-2.233; p = 0.001 ) were independent predictors of high SS. In receiver operating characteristic curve, the area under the curve of miR-208b and miR-499 in prediction of high SS was 0.775 and 0.713, respectively. Conclusions. Higher plasma levels of miR-208b and miR-499 were positively associated with the severity of CAD, and plasma miR-208b and miR-499 can act as potential biomarkers for estimating the severity of CAD.